Pemanfaatan Teknologi Biometrik Olahraga untuk Memantau Adaptasi Fisiologis Atlet Bulutangkis Selama Latihan Intensitas Tinggi - Muhammad Wahyono; Gatot Margisal Utomo; Ismawandi Bripandika Putra (MAN Insan Cendekia Jambi, 2026)
This study aims to examine the utilization of sports biometric technology to monitor physiological adaptations in badminton athletes during high-intensity training. A quasi-experimental research design with a pretest–posttest model was applied to 30 badminton athletes who participated in a structured high-intensity training program. Physiological parameters observed included resting heart rate, recovery time, and heart rate variability, which were recorded using an integrated wearable-based physiological monitoring system. Data were collected before and after the training intervention period and analyzed using descriptive and inferential statistical approaches to identify changes in physiological adaptation. The results demonstrated significant improvements in athletes’ physiological adaptation following high-intensity training, indicated by reduced recovery time, enhanced cardiovascular response efficiency, and improved heart rate stability after exercise. These findings suggest that sports biometric technology provides objective and real-time insights into athletes’ physiological responses throughout the training process. In conclusion, the application of sports biometric technology is effective as a supportive tool for monitoring the physical condition of badminton athletes and serves as a data-driven basis for coaches in optimizing training load management with greater precision.